O Papel da Atividade Discursiva no Exercício do Controle Social (Cadernos de Linguagem e Sociedade, 2010)
This article proposes that genres function as an integral part of socially organized activities and lend themselves to various types of social control, including the exercise of power. However, if the control exercised by genres is inevitable, it is not deterministic, since genres are historical, cultural and situated. Therefore, there remains space both for genre creativity and change as entities that are malleable, flexible and fit for discursive activity in daily life.